Climate change and shallow aquifers - unravelling local hydrogeological impacts and groundwater decline-induced subsidence - Guzy, A.; Piasecki, A.; Witkowski, W. T. (Elsevier, 2025)
Climate change significantly compromises global water resources, particularly shallow aquifer systems, which are vulnerable to variations in precipitation and evapotranspiration. This study investigated the impacts of climate change on a shallow aquifer system in the Gniezno Lakeland, Poland, by analysing the relationship among ground motion, hydraulic head changes, surface water variations, and meteorological trends. We used EGMS-based InSAR ground motion products to detect subtle land surface displacements across the study area, combined with hydrogeological data, meteorological records, and surface water measurements. Our results revealed a slight but ongoing subsidence of −0.9 mm/year across the area, with variations observed across different land cover types and wetlands being the most affected. Seasonal oscillations in hydraulic head (8–50 cm) and ground motion (2–7 mm) highlighted the aquifer's elastic response to climate variability. Long-term meteorological data indicated a trend towards a drier climate, with annual increases in temperature (+0.5 °C), insolation (+6.8 h), and evaporation (+3.8 mm), coupled with decreasing humidity (−0.13 %/year). The annual negative vertical water exchange, exceeding the volume of groundwater extraction, suggests that climate-driven factors are the primary drivers of aquifer storage decline. The aquifer system exhibited greater resilience to climate change than surface water, as evidenced by its annual storage change (∼2 % of lake volume fluctuations). Localized subsidence patterns near the lake shoreline further underscored the interplay between surface water and groundwater in this region. Our findings provide insights into the impacts of climate change on shallow aquifer systems and highlight the importance of integrating multisource data for comprehensive hydrogeological assessments.